The Internalization of Dongkrek Value to Strengthen Cultural Resilience (Research, Society and Development, 2019)
This study is aimed to identify the value of Dongkrek's art, describe and analyze the internalization efforts in strengthening cultural resilience. Descriptive qualitative approach is used as method and it is conducted for eight months in Madiun Regency, Indonesia. The data source used was primary and secondary data. Informants were determined by purposive sampling. Further, the data were collected through interview, observation and documentation technique. In addition, the data validity used triangulation and analyzed by interactive analysis model of Miles and Huberman. The result of this research revealed that (1) Dongkrek art has spiritual, heroism, leadership and aesthetics values. These values have the potential to strengthen cultural resilience and thus need to be internalized; and (2) there are various internalization efforts that have been implemented, such as: making Dongkrek art as the source of learning material of curricular activities, making Dongkrek art as mandatory extracurricular activity, hosting festival, publishing text book and pop-up, promoting by souvenir and modifying Dongkrek art. Thus, Dongkrek art values potentially served as a source to strengthen cultural resilience if they could be internalized and manifested properly in real life. Further, Dongkrek art were pride of Madiun society and Indonesia. Dongkrek art could strengthen and firmed attitude in maintaining indigenous culture from foreign cultural influences that could damage or endanger the national identity.